Visual Impact in the Urban Environment. The Case of Out-of-Scale Buildings - Fabrizio, Enrico; Garnero, Gabriele (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Recently, there has been an increasing need to apply methods for the estimation of the visual impact of buildings that are out-of-scale on its surrounding urban space, such as skyscrapers. In this paper, a method developed by the authors for the visual impact of buildings based on the viewshed analysis is applied to the out-of-scale buildings of the city of Turin. The method goes beyond the sole information if a cell is visible or not, which is typical of viewshed analyses, and also takes into account the various factors that cause the visual attenuation with the distance such as the visual acuity, the contrast between the target and the surrounding, the atmospheric visibility and the recognition process of the subject. The application of this methodology is done on two out-of scale buildings of the city of Turin – Italy (two skyscrapers, one of which is under construction, located in different areas of the city). From the visibility maps, in various conditions, it can be noted how the new buildings are or will recently be major landmarks not for the entire city but also for the surrounding municipalities.